Detection of Epithelial-Mesenchymal Transition Status of Circulating Tumor Cells in Patients with Esophageal Squamous Carcinoma. (26th June 2018) - Han, Dingpei; Chen, Kai; Che, Jiaming; Hang, Junbiao; Li, Hecheng
Abstract : Purpose . To investigate the correlation between the status of epithelial-mesenchymal transition (EMT) of circulating tumor cells (CTCs) and esophageal squamous cell carcinoma (ESCC). Methods . The demographic data and blood samples of 21 patients with ESCC were collected retrospectively. CTCs were enriched by using optimized CanPatrolTM CTC enrichment technique. CTCs were identified and characterized according to the EMT markers (e-CTCs: epithelial CTCs; mix-CTCs: epithelial-mesenchymal-mixed CTCs; m-CTCs: mesenchymal CTCs). The correlation between CTCs and demographic data was analyzed. Results . Total 129 CTCs were detected in all the patients: 11(8.5%) CTCs of them were e-CTCs, 76(58.9%) were mix-CTCs, and 42(32.6%) were m-CTCs. The average number of CTCs from each patient was6.1 ± 7.1 which included0.5 ± 0.9 of e-CTCs, 3.6 ± 5.2 of mix-CTCs, and2.0 ± 2.7 of m-CTCs; the difference between the three groups was significant (P = 0.017 ): the number of total CTCs was correlated with the number of mix-CTCs (R 2 = 0.883, P < 0.01 ) and m-CTCs (R 2 = 0.639, P < 0.01 ) but not e-CTCs (R 2 = 0.012, P = 0.641 ) and the number of CTCs was correlated with the N stage and TNM stage in this study (R 2 = 0.698 andR 2 = 0.359 ). Conclusions . Mix-CTCs and m-CTCs might play an important role in progression of ESCC; the number of CTCs in ESCC might have the potential to be a predictor of prognosis.